SIMILARITIES AND DIFFERENCES OF PERSON IN ENGLISH AND UZBEK LANGUAGE GRAMMAR - ASATOVA AZIZA (TADQIQOTLAR.UZ, 2024)
The concept of "Person" is a fundamental part of the grammatical structure in both English and Uzbek languages. However, the way this concept is expressed and applied in the two languages exhibits both similarities and differences. This study examines the treatment of "Person" in the grammar of English and Uzbek, focusing on the categories of personal pronouns, verb conjugation, and other grammatical devices that encode person. The analysis reveals that both languages have a similar three-way distinction between first, second, and third person. However, Uzbek has a more complex pronominal system with additional distinctions such as politeness levels. The systems of verb conjugation to mark person also show divergences, with Uzbek verbs exhibiting richer person-number inflections compared to the more analytic person marking in English.The paper discusses how these grammatical differences in the expression of "Person" between the two languages arise from their distinct typological and historical backgrounds. The findings contribute to a better understanding of cross- linguistic variation in the domain of person grammar and have implications for translation, language teaching, and contrastive linguistic analysis.